2007
DOI: 10.1111/j.1467-8659.2007.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time homogenous translucent material editing

Abstract: This paper presents a novel method for real-time homogenous translucent material editing under

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…In general however, these techniques di er from ours: they aim at obtaining interactive but approximate responses to edits, be it directly in the material parameter space [Song et al 2009;Wang et al 2008;Xu et al 2007] or inversely by posing constraints on the appearance [Hašan and Ramamoorthi 2013].…”
Section: Materials Editingmentioning
confidence: 99%
See 1 more Smart Citation
“…In general however, these techniques di er from ours: they aim at obtaining interactive but approximate responses to edits, be it directly in the material parameter space [Song et al 2009;Wang et al 2008;Xu et al 2007] or inversely by posing constraints on the appearance [Hašan and Ramamoorthi 2013].…”
Section: Materials Editingmentioning
confidence: 99%
“…Initial works use precomputed radiance transfer (PRT) to globally change bulk scattering and absorption parameters [Wang et al 2008;Xu et al 2007]. Extending these PRT-based approaches to heterogeneous materials, however, would lead to an intractable dimensionality increase.…”
Section: Materials Editingmentioning
confidence: 99%
“…On the other hand, Xu et al (Xu, et al, 2007) demonstrated that the diffusion profile can be well approximated in real-time using a piecewise polynomial basis even though their method is also based on a numerical method. However, it needs an additional step to determine the optimal locations of the knots which link the polynomial basis.…”
Section: Diffusion Profile Approximationmentioning
confidence: 99%
“…In this work we focuses on developing a real-time editing system for multi-layered translucent materials by building up existing methods by Xu et al (Xu, et al, 2007) and Donner and Jensen (Donner and Jensen, 2005). We significantly reduce the computation time for the convolution process for the diffusion profiles by using the QFHT.…”
Section: Materials Editingmentioning
confidence: 99%
See 1 more Smart Citation